Localization of heme biosynthesis in the diatom Phaeodactylum tricornutum and differential expression of multi-copy enzymes - Yang, Shun-Min; Gruber, Ansgar; Jiroutová, Kateřina; Richtová, Jitka; Vancová, Marie; Tesařová, Martina; Masařová, Petra; Dorrell, Richard G.; Oborník, Miroslav (Frontiers in Plant Science, 2025)
Heme is essential for all organisms. The composition and location of the pathway for heme biosynthesis, have been influenced by past endosymbiotic events and organelle evolution in eukaryotes. Endosymbioses led to temporary redundancy of the enzymes and the genes involved. Genes were transferred to the nucleus from different endosymbiotic partners, and their multiple copies were either lost or retained, resulting in a mosaic pathway. This mosaic is particularly complex in organisms with eukaryote-derived plastids, such as diatoms. The plastids of diatoms are clearly derived from red algae. However, it is not entirely clear whether they were acquired directly from a red algal ancestor or indirectly in higher-order endosymbioses. In the diatom Phaeodactylum tricornutum, most enzymes of the pathway are present in a single copy, but three, glutamyl-tRNA synthetase (GluRS), uroporphyrinogen decarboxylase (UROD) and coproporphyrinogen oxidase (CPOX), are encoded in multiple copies. These are not direct paralogs resulting from gene duplication within the lineage but were acquired horizontally during the plastid endosymbioses. While some iso-enzymes originate from the host cell, others originate either from the genome of the cyanobacterial ancestor of all plastids or from the nuclear genome of the eukaryotic ancestor of the diatom complex plastid, a rhodophyte or an alga containing rhodophyte-derived plastids, a situation known as pseudoparalogy. Using green fluorescent protein-tagged expression and immunogold labeling, we experimentally localized all enzymes of the pathway in P. tricornutum, and confirmed their localization in the plastid, with a few possible exceptions. Our meta-analyses of transcription data showed that the pseudoparalogs are differentially expressed in response to nitrate starvation, blue light, high light, high CO2, and the cell cycle. Taken together, our findings emphasize that the evolution of complex plastids via endosymbiosis has a direct impact not only on the genetics but also on the physiology of resulting organisms.